Mathematical critical thinking ability based on self-concept in discovery learning model assisted by ispring suite - Ardhini, Rosa Ary; Rochmad, Rochmad; Asih, Tri Sri Noor (Desimal: Jurnal Matematika, 2022)
Students’ cognitive abilities were influenced by several affective abilities, one of them was self-concept. Critical thinking ability is an important ability in learning mathematics. The purpose of this research was to describe mathematical critical thinking skills based on self-concept in the discovery learning model assisted by iSpring Suite. This research used a qualitative method. The research subjects were grouped based on self-concept category, where each category is chosen by two students to analyze their mathematical critical thinking skills. This research collects data by using mathematical critical thinking skills tests, self-concept questionnaires, interviews, observation, and documentation. Data validity used the triangulation technique. Data analysis techniques were carried out by data collection, data reduction, data display, and verification. The results showed that students with a high self-concept category were able to fulfill every indicator at the steps of clarification, assessment, conclusion, and strategy. The medium self-concept category was able to fulfill the indicators during the clarification and assessment steps. Meanwhile, the low self-concept category only fulfills the indicators at the clarification step.